The art of knowledge sharing towards construction project success - Rosman, Muhammad Redza; Taharuddin, Nurul Shima; Ab Gani, Muhamad Abdul Aziz; Ibrahim, Nor Idayu; Md Nazri, Haslinda; Nazrin, Nizar; Abdullah, Anwar Fikri (Universiti Teknologi MARA, Perak, 2025)
The construction industry plays a central role in Malaysia’s development but continues to face persistent challenges such as delays, cost overruns, and inefficiencies, many of which are linked to fragmented knowledge management. This study addresses the first objective of a broader research project: to identify the knowledge sharing (KS) practices employed in construction projects, with a focus on Grade 7 contractors in Selangor. Drawing on literature and empirical evidence, eight KS practices were examined, including face-to-face interaction, formal practices, meetings, learning support, project briefings, phone calls, lessons learnt from previous projects, and ICT tools. A quantitative survey design was applied, yielding 270 valid responses from project managers, engineers, and site personnel. Data were analysed using descriptive statistics, with reliability and normality testing confirming robustness. The findings reveal that meetings, face-to-face interactions, and lessons learnt from past projects are the most dominant KS practices, while learning support and phone calls are less frequently utilised. ICT tools were moderately adopted, reflecting gradual digitalisation within the sector. Overall, the results demonstrate that KS in Malaysian construction is predominantly interpersonal and experiential, with digital mechanisms serving as complementary supports. These insights provide empirical confirmation of the hybrid nature of KS, blending formal and informal practices to sustain collaboration in complex project environments. The study concludes that institutionalising a balanced mix of these approaches is critical for improving project outcomes and enhancing the overall competitiveness of the Malaysian construction industry.